Synergetic effect of superabsorbent polymer (SAP) and crystalline admixture (CA) on mortar macro-crack healing. (30th June 2020) - Li, Desheng; Chen, Bing; Chen, Xihui; Fu, Bing; Wei, Hongchao; Xiang, Xiaorui
Graphical abstract: Highlights: SAP and CA were used together for crack healing of cement-based material. The factors affecting SAP healing efficiency were tested by rapid permeability test. The optimum crystalline admixture was explored for the complete closure. Microscopic morphology of healing products was observed through SEM. Abstract: The macro-crack is wide-spread in concrete structure, especially the width >0.5 mm, which is hard to be sealed with its self-healing capacity. This research investigated the synergetic effect of superabsorbent polymer (SAP) and crystalline admixture (CA) for macro-crack closure in cement-based materials (CBM). The affecting factors on SAP usage in CBM were studied, and the suitable CA was also explored for complete closure. The results indicated citric acid was an efficient additive for supplementary repair through promoting chemical precipitation. The optically and scanning electronically microscopic morphology also verified the hypothesis from data analysis. The leakage from macro-crack would facilitate the corrosion of reinforced steel and surrounding concrete. Hence, the optimum usage of combined CA and SAP is highly suggested, which is accessible and economical for macro-crack closure in waterproof projects.